2021
DOI: 10.35741/issn.0258-2724.56.6.43
|View full text |Cite
|
Sign up to set email alerts
|

HMG-Coa Reductase Inhibitory Activity of Extract and Catechin Isolate From Uncaria Gambir as a Treatment for Hypercholesterolemia

Abstract: The article describes a new idea of plant-based hypercholesterolemia treatment. Statins are commonly used for hypercholesterolemia treatment. Due to the side effects of statins, natural HMG-CoA reductase inhibitors plant-based are needed. Based on the affordability and less toxicity, the plant has increasing acceptability for treating ailments. The 3-hydroxy-3-methyl-glutaryl-coenzyme A (HMG-CoA) reductase is the key enzyme of the mevalonate pathway producing cholesterol. Inhibition of HMG-CoA reductase reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Catechin (C 15 H 14 O 6 ; Molecular mass: 290.26) (Figure 1) is a polyphenol compound available in several plants including Potentilla species which has antioxidant activity and is used as a memory enhancer and for lowering the cholesterol in the blood [19][20][21]. In the study conducted by Ganguly et al [22] and Choudhary et al [17] the catechin showed potent anticancer and antioxidant activity respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Catechin (C 15 H 14 O 6 ; Molecular mass: 290.26) (Figure 1) is a polyphenol compound available in several plants including Potentilla species which has antioxidant activity and is used as a memory enhancer and for lowering the cholesterol in the blood [19][20][21]. In the study conducted by Ganguly et al [22] and Choudhary et al [17] the catechin showed potent anticancer and antioxidant activity respectively.…”
Section: Introductionmentioning
confidence: 99%